AN UPTO DATE REVIEW: IN SIGHTS OF DIABETIC WOUND HEALING - VISHESH KUMAR MAURYA; Shweta Rawat; Ravinder Pal Singh; Abhilasha Mittal; Sanjesh Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Diabetes mellitus is a chronic metabolic condition characterized by persistent hyperglycemia, which has a detrimental impact on long-term health. The prevalence of diabetes mellitus is increasing, leading to a rise in the number of individuals experiencing impaired wound healing associated with this condition. Diabetic wounds often result in lower limb amputations, causing significant financial burden. The healing of these wounds is particularly challenging due to the hyperglycemic environment that promotes the growth of biofilms. This review provides an overview of recent advancements in the understanding of the pathophysiology of diabetic wounds, with a focus on neuropathy, impaired angiogenesis, compromised barrier function, and subsequent polymicrobial infections. The elucidation of these mechanisms contributes to a better understanding of the complexities involved in diabetic wound healing. Furthermore, this review discusses current treatment approaches as well as potential future strategies aimed at addressing the diverse pathologies associated with diabetic wounds. By targeting specific aspects of the wound healing process, these interventions aim to promote more efficient and effective healing, ultimately reducing the need for amputations and improving patient outcomes. Given the alarming increase in the prevalence of diabetes, it is crucial to stay updated on the advancements in our understanding of diabetic wound pathophysiology and the development of novel therapeutic approaches. Continued research and innovation in this field hold promise for improving the management and outcomes of individuals with diabetic wounds, thus alleviating the burden associated with this debilitating complication.